Stroke prevention and control system in China: CSPPC-Stroke Program. Issue 3 (April 2021) - Chao, Bao-Hua; Yan, Feng; Hua, Yang; Liu, Jian-Min; Yang, Yi; Ji, Xun-Ming; Peng, Bin; Zhao, Guo-Guang; Wang, Yong-Jun; Kang, De-Zhi; Wang, Yi-Long; Zeng, Jin-Sheng; et al.
In China, stroke is a major cause of mortality, and long-term physical and cognitive impairment. To meet this challenge, the Ministry of Health China Stroke Prevention Project Committee (CSPPC) was established in April 2011. This committee actively promotes stroke prevention and control in China. With government financial support of 838.4 million CNY, 8.352 million people from 536 screening points in 31 provinces have received stroke screening and follow-up over the last seven years (2012–2018). In 2016, the CSPPC issued a plan to establish stroke centers. To shorten the pre-hospital period, the CSPPC established a stroke center network, stroke map, and stroke "Green Channel" to create three 1-h gold rescue circles, abbreviated as "1-1-1" (onset to call time <1 h; pre-hospital transfer time < 1 h, and door-to-needle time < 1 h). From 2017 to 2018, the median door-to-needle time dropped by 4.0% (95% confidence interval (CI), 1.4–9.4) from 50 min to 48 min, and the median onset-to-needle time dropped by 2.8% (95% CI, 0.4–5.2) from 180 min to 175 min. As of 31 December 2018, the CSPPC has established 380 stroke centers in mainland China. From 1 November 2018, the CSPPC has monitored the quality of stroke care in stroke center hospitals through the China Stroke Data Center Data Reporting Platform. The CSPPC Stroke program has led to a significant improvement in stroke care. This program needs to be further promoted nationwide.